Health Education and Blood Pressure and Blood Sugar Checks in RW 4 Jayagiri Village, Lembang, West Bandung - Andriana, Sari Sarce; Ngadiran, Antonius; Sinaga, Saurmian; Natalia, Lidya; Hotmaida, Linda; Widiastuti, Yuliati; Yeni, Yeni (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
Health is a human right and an investment for successful nation building. For this reason, it is necessary to carry out comprehensive health development in order to realize a healthy society. This service aims to increase public knowledge about the symptoms, complications, and prevention of hypertension and diabetes mellitus. The method carried out in this service is to use the method of health examination and health counseling. The stages of implementation in this service activity are divided into 6 parts, namely: the licensing stage, coordination with cadres and RW leaders, medical examinations, reading results, counseling, and evaluation. Evaluation is carried out by 2 methods, namely the pre-test and post-test methods. The results of counseling and examination can have a positive impact on the community, especially for the health of the elderly. The results of the examination at this community service activity from 47 people found 70% abnormal blood pressure (> 120/90 mmHg) and 10.4% abnormal blood sugar (>200). People whose Blood Pressure and Blood Sugar are not normal are encouraged to carry out further health checks at the Puskesmas. The conclusion obtained from this community service activity is that there was an increase in community knowledge from the sufficient category in the pre-test before 32.4% to 51.4% and a decrease in the knowledge category from less than 40.5% to 24.3%.